Lingual cysticercosis - S C Pandey; S D Pandey (Indian Journal of Plastic Surgery)
A fourtyfive year old male presented with a painless solitary nodular swelling near left lateral border of the tongue of two months duration. Fine needle aspiration cytology lead to no conclusion. Excisional biopsy was done. Histopathology revealed Cysticercosis cellulosae and the parasite could be visualised in the slide along with the tongue muscles.